A lamda-optimal based heuristic for the berth scheduling problem - Golias, Mihalis; Boilé, Maria; Theofanis, Sotirios (My University, 2010)
Berth scheduling aims to optimally schedule vessels to berthing areas along a quay and is a complex optimization problem. In this paper we propose a lamda-optimal based heuristic as a resolution approach for the discrete space berth scheduling problem. The proposed heuristic can also be applied to validate optimality, in the case where other (meta)heuristics are applied as resolution approaches. A second internal Genetic Algorithms based heuristic is also proposed to reduce the computational time required for medium to large scale instances. Numerical experiments performed show that the proposed heuristic is adequate to produce near-optimal results within acceptable computational times. © 2009 Elsevier Ltd.
Keywords: Container terminal operations; Berth scheduling; Optimization; Heuristics